2000
DOI: 10.1517/14656566.1.4.737
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer staging and adjuvant chemotherapy

Abstract: Colorectal cancer is a significant cause of morbidity and mortality in Western populations. The standard of care for staging patients with colorectal cancer to determine prognosis and identify patients who will receive adjuvant therapy continues to be histopathology of regional lymph nodes. However, the significant variability in survival within each staging category likely reflects the heterogeneity of detecting micrometastatic disease employing this technique. Novel molecular markers of micrometastases curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 77 publications
0
27
0
Order By: Relevance
“…The most important determinant for predicting survival in patients with colorectal cancer is the presence of tumor cells in regional lymph nodes and evaluation of those nodes for metastatic disease is a central component of all colorectal cancer staging schema [2]. Cancer stage at diagnosis not only determines prognosis, but also guides selection of patients to receive adjuvant chemotherapy [2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most important determinant for predicting survival in patients with colorectal cancer is the presence of tumor cells in regional lymph nodes and evaluation of those nodes for metastatic disease is a central component of all colorectal cancer staging schema [2]. Cancer stage at diagnosis not only determines prognosis, but also guides selection of patients to receive adjuvant chemotherapy [2].…”
Section: Discussionmentioning
confidence: 99%
“…Cancer stage at diagnosis not only determines prognosis, but also guides selection of patients to receive adjuvant chemotherapy [2]. Despite the critical importance of lymph node involvement, sensitive and specific techniques to assess regional lymph node micrometastases are lacking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the heterogeneity of therapeutic benefit in pN0 patients may reflect a contribution of inaccurate staging [4,5,21,24,[43][44][45]. In our prospective trial [45], GUCY2C qRT-PCR identified a subset of pN0 patients whose clinical outcomes matched that of stage III patients, staged by established criteria.…”
Section: Future Considerationsmentioning
confidence: 88%
“…This uncertainty of therapeutic 8 benefit is reflected in the evolution of treatment guidelines, in which adjuvant therapy is optional in pN0 patients with clinicopathologic characteristics suggesting poor prognostic risk [9,[40][41][42]. Heterogeneous responses to therapy in pN0 patients reflect, in part, the variability of occult lymph node metastases [4,5,21,24,[43][44][45]. Consequently, there is an unmet clinical need for better methods that detect prognostic occult nodal metastases, to identify pN0 patients who could benefit from adjuvant therapy [6,38] and who are candidates for pharmacogenomic testing to identify critical mutations defining responses to molecular targeted agents [46].…”
Section: Adjuvant Therapy In Colon Cancermentioning
confidence: 99%